Pelatihan Digitalisasi Perencanaan dan Pengendalian Produksi Batik di Sanggar Batik Kembang Mayang - Mayusda, Idriwal; Akbari, Annisa Dewi; Sasongko , Agung; Suhardini, Didien; Ismail, Muhammad Luthfi; Kaban, Dion Timothy (Abdimas Universal, 2025)
The recognition of Batik as one of Indonesia's Oral and Intangible Heritage of Humanity by UNESCO has increased interest in batik products both locally and internationally. The batik industry has also developed into one of the development priorities because it has leverage for national economic growth. Sanggar Batik Kembang Mayang is one of the MSMEs that not only produces batik cloth but also provides educational tourism facilities for the batik-making process. Sanggar Batik Kembang Mayang faces problems related to less-than-optimal raw material management. This manual recording system is prone to errors and affects the production process. Therefore, the Faculty of Industrial Technology, Trisakti University, conducted a Community Service (PkM) program with the theme of Digitalization Training for Batik Production Planning and Control. The form of PkM activities is training on the process of planning and controlling batik production as well as the application of the process of managing raw materials and orders with the MS. Excel application. The training results showed that 67% of participants strongly agreed that the training was interesting and useful. In terms of understanding the material, 56% of participants also stated that they understood enough, and 33% answered that they understood production planning and control very well.